Computer assisted human karyotyping an analysis of 131 cases - Rahman, Md Mizanur; Giti, Susane; Islam, Md Saiful; Shaha, Debashish; Yousuf, AKM Abu; Bhuyain, Mohammad Nuruzaman; Khatun, Nasima; Kawsar, Narjis Maliha (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Karyotyping is the process of pairing and ordering all the chromosomes of an organism, thus providing a genome-wide snapshot of an individuals chromosome. G-banded karyograms are routinely used to diagnose a wide range of chromosomal abnormalities in individuals. Although the resolution of chromosomal changes detectable by G-banded karyotyping is typically a few megabases, this can be sufficient to diagnose certain categories of abnormalities. Objectives: The primary aim of this study was to investigate the different types of chromosomal aberrations and their relative frequencies in a group of referred patients with suspected genetic disorders. Methods: This observational study was carried out at Armed Forces Institute of Pathology (AFIP) for a period of two years from January 2011 to December 2012. A total of 131 patients were included in this study. These patients were referred to AFIP from different Combined Military Hospitals (CMH) of Bangladesh Army and also from civil medical installations. All the patients were subjected to full genetic study; complete genetic examination and pedigree construction was done to exclude nonchromosomal causes of anomaly. Detailed history and physical findings were also noted in a prescribed format. The study included peripheral lymphocyte culture by a standard method using the Gbanding technique. 32 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Results: Out of 131 patients, 54 (42.2%) were male and 77 (57.8%) were female with male to female ratio 0.7:1. The age limit of the patient ranges from 04 days to 70 years. Most of the patients (32.1%) were in the age group of 010 years followed by 2130 year age group (30.5%). Consanguineous marriage was found in 15 (11.5%) cases in which 3 (2.3%) cases had chromosomal aberrations. Recurrent abortion was the main clinical indication (18.3%) followed by infertility (15.3%). Chromosomal aberrations were detected in 26 patients (19.8%); of these, 20 (15.2%) involved autosomes, while only 6 (4.6%) involved gonosomes. Trisomy 21 was detected in 12 (9.1%) patients and Philadelphia chromosome was found in 8 (6.1%) patients. Turner syndrome was detected in 5 (3.8%) patients and Klinefelter syndrome was found in 1 (0.8%) patient. Conclusion: The precise delineation of different types of chromosomal aberrations is only possible using clinical examination and advanced cytogenetic tools by experienced cytogeneticists. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21823 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013